Evaluation Of Illness Perceptions And Their Associations With Glycaemic Control, Chronic Kidney Disease And Medication Adherence In Type 2 Diabetes Mellitus Patients At Hospital Pulau Pinang - Balasubramaniam, Shamila (2018)
Malaysia has a high prevalence of diabetes at 16.9% and suboptimal glycaemic control with only 23.8% achieving HbA1C of <7%. Illness perceptions (IP) involve coping strategies and behavioural responses that influence glycaemic control. The objective of this study was to evaluate IP and their associations with glycaemic control, chronic kidney disease (CKD) and medication adherence in Type 2 diabetes mellitus patients (T2DM). A cross-sectional study was conducted in a purposive sample of 384 T2DM patients using Revised Illness Perception Questionnaire and 8-Item Morisky Medication Adherence Scale. T2DM patients >18 years under regular follow-up were included.